2005
DOI: 10.1155/s1110662x0500005x
|View full text |Cite
|
Sign up to set email alerts
|

UV/VIS spectral properties of novel natural products from Turkish lichens

Abstract: Abstract. UV/VIS spectral characteristics of three new biologically active natural products, isolated from Turkish lichens, have been investigated in solvents of various polarity and proton donating ability. The effect of the solvent on spectral characteristics has been estimated. Quantum chemical calculations with the optimization of molecular geometry were done with the full-valent semiempirical methods AM1 and PM3 for conformational analysis and in order to discuss the charge distributions and dipole moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The ground-state UV/vis absorption spectra of 1 (thick line), NDI (thin solid line), and Pt(phen)Cl 2 (thin dashed line) are depicted in Figure . The absorption spectrum of NDI is dominated by a transition to the lowest excited singlet S 1 state of NDI , in the range 320−390 nm with the well-resolved vibronic structure. The spectrum of Pt(phen)Cl 2 contains an intense intraphenanthroline absorption at about 260 nm, and an MLCT absorption band at 395 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The ground-state UV/vis absorption spectra of 1 (thick line), NDI (thin solid line), and Pt(phen)Cl 2 (thin dashed line) are depicted in Figure . The absorption spectrum of NDI is dominated by a transition to the lowest excited singlet S 1 state of NDI , in the range 320−390 nm with the well-resolved vibronic structure. The spectrum of Pt(phen)Cl 2 contains an intense intraphenanthroline absorption at about 260 nm, and an MLCT absorption band at 395 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Many microbiological activity studies of some lichens explain the activities on gram (+) and gram (-) bacteria and fungi [13][14][15]. Two studies on Turkish lichens explain the isolation and structural determination of some natural products and their fluorescence emission properties, and some of them describe the volatile compounds of some lichens [16,17]. In the present study, the chemical composition of apolar phases of the above lichens was reported by a gas chromatography-mass spectrometry (GC-MS) combined system, and the results were examined in terms of EFAs and their importance for a healthy diet.…”
mentioning
confidence: 99%